DETERMINATION OF PHYSICO-CHEMICAL PARAMETERS OF WATER IN BIOLOGICAL MINIMUM IN THE LAKE ”RADONIQ” - Xhelal Kepuska; Luan Daija; Ilir Kristo (European Scientific Journal, ESJ, 2014)
Artificial lake of Radoniqi is raised in dam of river Përrua in north of the town of Gjakova , in village Radoniq , main source of supply with water is “Lumbardhi i Deçanit” it secure with water near 90%.Goal of this study was to analyzed concentration of physical parameters, chemical and metals in the water of Lake Radoniq and their impact on water quality. Rating of physical parameters, chemical and metal is important to determining the environmental condition of waters. The general content of metals, organic substances in water provides valuable information not only for the general level of pollution in the water, but also helps in determining the pollutant source.In this study that has been done over the years 2011,2012, has been presented results of physical-chemical parameters and metals like: Fe,Pb,Zn,Al in the water of Lake Radoniqi that after treatment this water is used for human consume. The results that has been obtained show that the water of the lake "Radoniq" is water with good quality , but the presence of some metals such as Cd, Pb, Zn, etc. in the lake water makes us think about their sources and to search for a better solution. Therefore required continuous monitoring and deeper analyze for quality of water. Certainly water needs to be treated in technological process so it can be used for human consume. Biological minimum is designed under the lake, where water discharges collected from all seen that certain parameters of water quality by biological minimum is almost the same features as the lake naturally seen a lower presence of dissolved oxygen , what is more than normal because of the depth of approximately - 68 m. Therefore, it requires continuous monitoring and deeper analysis of water quality.